Implementasi Kepemimpinan Transformasional sebagai Upaya Peningkatan Kualitas Madrasah Ibtidaiyah Negeri 1 Temanggung - Murti, Roso; Sabarudin, Sabarudin (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2023)
This study aims to examine the implementation of transformational leadership in an effort to improve the quality of madrasah. There is a fundamental change in the world of education, namely from a centralized management system to a decentralized management system. This requires various adjustments and changes in various aspects of the madrasa as well as the pattern and style of leadership. efforts to improve and improve the quality of madrasah are something that is very important to do immediately. Therefore, to realize the right and quality of madrasah, adequate leadership is needed. The implementation of transformational leadership is applied to Public Elementary School 1 Temanggung. The results of this study are that Madrasah Ibtidaitah Negeri 1 Temanggung under the leadership of Muh Junaidi, S. Ag. M.Pd underwent various transformations. Changes and updates have covered all standards which include standards for content, processes, graduate competencies, training, infrastructure, management, financing and assessment. With this achievement, the quality of madrasas is increasing in all fields.